Active commuting to and from school among 106, 605 adolescents in 27 Asia-Pacific countries. (December 2019) - Uddin, Riaz; Mandic, Sandra; Khan, Asaduzzaman
Abstract: Introduction: Active school commuting (ASC) can be a promising strategy to promote physical activity among the Asia-Pacific adolescents. This study examined the prevalence of ASC by age, sex, and country income among adolescents from the Asia-Pacific region. Methods: Data from the Global School-based Student Health Survey, collected between 2007 and 2016, from 27 Asia-Pacific countries, were analysed. Country-specific weighted prevalence of ASC (defined as walking or bicycling to and from school on ≥3 days/week) were computed. Pooled estimates of ASC were computed using random effects meta-analysis. Spearman correlational analysis was used to assess association of ASC prevalence with common global indices. Results: Data were available for 106, 605 adolescents (mean age 14.7 [SD 1.28] years, 52.0% male). Overall, the pooled prevalence of ASC was 42.1% (95% CI 36.7-47.6). The highest prevalence of ASC was in Vietnam and lowest in Timor Leste with six countries reporting the prevalence >50.0%. Males had significantly higher odds of using ASC than females in seven countries, while females had significantly higher odds in two countries. Compared to younger adolescents (13–15 years), older adolescents (16–17 years) had significantly higher odds of using ASC in six countries, and lower odds in seven countries. The pooled prevalence of ASC was 48.9% (40.9-56.9) in lower-income-, 33.3% (29.4-37.2) in upper-middle-income- and 27.4% (13.7-41.1) in high-income-countries. Prevalence of ASC was negatively associated with country's Gini coefficient (rho = −0.50, p = 0.04). Conclusions: Across the Asia-Pacific region, two out of five adolescents engaged in ASC with large variability between the countries as well as by age and sex. Future research should examine multiple factors that influence cross-country variations in adolescents' ASC, which can inform country-specific interventions and policies to promote ASC in the Asia-Pacific region. Highlights: Two in five adolescents used active commuting to and from school on ≥3 days/week. Males had higher odds of using active commuting than females in many countries. Use of active commuting decreased with the increase of country's income. Active commuting was negatively associated with country Gini coefficient.